Low‐Frequency‐Noise Spectroscopy of TaOx‐based Resistive Switching Memory. (2nd November 2021) - Sugawara, Kota; Shima, Hisashi; Takahashi, Makoto; Naitoh, Yasuhisa; Suga, Hiroshi; Akinaga, Hiroyuki
Abstract: Research and development into resistive switching memories, such as resistive random access memory (ReRAM) and memristors, are being actively promoted toward the realization of new computing techniques. To improve the reliability of these devices, it is important to clarify their resistance characteristics. Low‐frequency‐noise spectroscopy (LFNS) is a powerful method for investigating the nature of traps in conduction paths, even at the nanoscale. In this article, the results of LFNS measurements on a TaOx‐based ReRAM device are presented. The temperature dependence of the noise spectra at given frequencies reveals the existence of multiple trap levels, which are observed over a wide range of resistance values. These experimental results show that the ReRAM device is particularly advantageous when used in analog resistive switching applications. Abstract : Low‐frequency‐noise spectroscopy revealed that multiple trap levels exist and that these trap states can be observed in a wide resistance range of a TaOx‐based ReRAM device. The experimental results indicate that the ReRAM device is superior, particularly when used in analog resistive switching applications.